2013
DOI: 10.1021/ma4015033
|View full text |Cite
|
Sign up to set email alerts
|

A Mild and Efficient Approach to Functional Single-Chain Polymeric Nanoparticles via Photoinduced Diels–Alder Ligation

Abstract: We present a new ambient temperature synthetic approach for the preparation of single-chain polymeric nanoparticles (SCNPs) under mild conditions using a UV-light-triggered Diels–Alder (DA) reaction for the intramolecular cross-linking of single polymer chains. Well-defined random copolymers with varying contents of styrene (S) and 4-chloromethylstyrene (CMS) were synthesized employing a nitroxide-mediated radical polymerization (NMP) initiator functionalized with a terminal alkyne moiety. Postpolymerization m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 63 publications
3
101
0
1
Order By: Relevance
“…Many groups have examined similar chemistry in SCNP synthesis. 31 UPy dimerization has been used to study the effect of several variables in SCNP formation. This is demonstrated in several publications by Meijer and coworkers involving 2-uriedopyrimidinone (UPy) dimerization (Fig.…”
Section: Non-covalent Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Many groups have examined similar chemistry in SCNP synthesis. 31 UPy dimerization has been used to study the effect of several variables in SCNP formation. This is demonstrated in several publications by Meijer and coworkers involving 2-uriedopyrimidinone (UPy) dimerization (Fig.…”
Section: Non-covalent Chemistrymentioning
confidence: 99%
“…Light scattering is an absolute method; the molar mass of large macromolecules is calculated based on first principles and consequently does not produce data relative to standards. 31,37,80 Viscometry Another valuable technique in the characterization of SCNPs is solution viscometry. Work from our laboratory has shown that using a MALS detector in-line with an SEC can prove that the molecular weight is consistent from parent polymer to SCNP.…”
Section: Light Scatteringmentioning
confidence: 99%
“…8,117 In this sense, the morphology change suffered by SCNPs on passing from solution to the solid state is of paramount importance for the construction of efficient biosensors based on immobilized protein-mimic nano-objects and for the development of transient vitamin-binding systems, among other applications (see Section 3). 8,117 In this sense, the morphology change suffered by SCNPs on passing from solution to the solid state is of paramount importance for the construction of efficient biosensors based on immobilized protein-mimic nano-objects and for the development of transient vitamin-binding systems, among other applications (see Section 3).…”
Section: Single Chain Nanoparticlesmentioning
confidence: 99%
“…UV light‐induced cycloadditions often constitute an alternative, convenient, atom‐efficient reaction class for single‐chain folding that can be carried out quantitatively at ambient temperature without the need for any metal catalyst. A number of photoinduced reactions have been examined for SCNP formation, including the light‐induced Diels–Alder reaction (DA; strictly speaking, the photochemical provision of an ene or diene species, which subsequently under goes a rapid ambient temperature DA reaction), the photoinduced nitrile‐imine mediated tetrazole‐ene cycloaddition, the photodimerization of anthracene, as well as the photodimerization of coumarin . Light‐triggered protocols, especially at higher wavelengths, are particularly attractive if, during the self‐folding process, temperature‐sensitive molecules are to be included into the SCNP.…”
Section: Repeat Unit Folding: Latest Developmentsmentioning
confidence: 99%